Kelekatan Orang Tua dengan Kemandirian Remaja pada Siswa MTsS - Harri Kurniawan; Ria Okfrima; Agustina Putry (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2022)
The bond between parents and children really needs to be built. Attachment of parents and children is important in increasing independence in adolescents. Adolescents high independence helps them to make their own decisions both academically and in other aspects of life. The independence of students can also make students do whatever they want. This study aims to examine the attachment of parents to adolescent independence in grade VII and IX students located at MTsS Nurul Yaqin Siti Manggopoh, Lubuk Basung district. The independent variable used in this research is the scale of parental attachment and the dependent variable is Student Independence. The measuring instrument used in this research is the scale of attachment and independence. The technique taking sampling used in research this is saturated sampling. The number of samples in the study amounted to 50 students. Validity test using Corrected Item-Total Correlation and reliability test using Alpha technique Cronbach. The test results show that the coefficient of validity on the scale of attachment ranges from 0.318 to 0.789, while the coefficient reliability is 0.891 The results. The coefficient of validity on the independence scale ranges from 0.336 to 0.819, while the reliability coefficient is 0.897. Based on the results analysis data show size. This means that there is a significant relationship with a positive direction between Parental Attachment and Adolescent Independence in grades VII and IX at MTsS Nurul Yaqin Siti Manggopoh, Lubuk Basung district. So it can be interpreted that the hypothesis in this study is accepted. The effective contribution of attachment and independence variables was 27%.